1980
DOI: 10.1073/pnas.77.8.4726
|View full text |Cite
|
Sign up to set email alerts
|

Location of the chromophore in bacteriorhodopsin.

Abstract: We present a location for the retinylidene chromophore in dark-adapted bacteriorhodopsin based on the differences in neutron scattering between purple membrane preparations reconstituted with retinal and with deuterated retinaL The Fourier difference density map contains more peaks than expected, and additional arguments are introduced to exclude artificial peaks caused by the reconstitution techniques or the limited resolution of the diffraction data. The membrane preparation used is necessarily dark-adapted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
29
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 32 publications
5
29
1
Order By: Relevance
“…All four studies concluded that the chromophore is located in the interior of bacteriorhodopsin. A clear discrepancy exists between the results of King et al (4) and Jubb et al. (7) concerning the location of the 0-ionone ring.…”
contrasting
confidence: 52%
See 2 more Smart Citations
“…All four studies concluded that the chromophore is located in the interior of bacteriorhodopsin. A clear discrepancy exists between the results of King et al (4) and Jubb et al. (7) concerning the location of the 0-ionone ring.…”
contrasting
confidence: 52%
“…Thus far, the position of retinal could not yet be resolved by the latter method. In a pioneering study, King et al (4) determined this location, projected onto the plane of the membrane, by means of neutron diffraction with perdeuterated retinal containing 28 deuterons. Three main peaks were observed in the Fourier difference map and an unambiguous assignment was difficult.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The peptides (l-lo), (1 l-13) (14-24) and (25)(26)(27)(28)(29)(30) belonging to the N-terminal fragment were found in the supernatant. Papain action on the inside-out membranes cleaved another bond, 186-187.…”
mentioning
confidence: 99%
“…Various physical methods, such as neutron diffraction [28] or fluorescence [29] provided some information about spatial arrangement of the /! !-ionone ring.…”
mentioning
confidence: 99%